Staggered cold-water coral mound build-up on an Alboran ridge during the last deglacial (East Melilla Mound Field, western Mediterranean) - Fentimen, Robin; Feenstra, Eline J.; Rüggeberg, Andres; Hall, Efraim; Rosso, Antonietta; Hajdas, Irka; Jaramillo-Vogel, David; Grobéty, Bernard; Adatte, Thierry; Van Rooij, David; Frank, Norbert; Foubert, Anneleen (Marine geology, 2023)
The start-up, build-up and demise of cold-water coral mounds are governed by environmental changes at global, regional and local scales. Whilst the formation of cold-water coral mounds across the globe is widely documented to follow interglacial-glacial cycles, less is known about their response to local environmental fluctuations during short time intervals. This study investigates the local variations in coral mound build-up along Brittlestar Ridge I (East Melilla Coral Province, Southeast Alboran Sea) by comparing three on-mound gravity cores collected ∼1 km apart, together with five previously described on-mound records, along a longitudinal transect on the ridge crest. ...
Online veröffentlicht am 13. Februar 2023
Gesehen am 12.12.2023